The development of simple fuzzy system using VHDL / Mohd Hafizuddin Omar - Omar, Mohd Hafizuddin (2004)
This project describes the implementation of a fuzzy controller in Hardware- Description Language (HDL). The motivation behind the implementation of a fuzzy controller was driven by the need for an inexpensive hardware implementation of a generic fuzzy controller for use in industrial and commercial application. In this project, Very High speed integrated-circuit Hardware-Description Language (VHDL) has been used for the hardware description and this application is suitable for being implemented into an Application Specific Integrated Circuit (ASIC) or Field Programmable Gate Array (FPGA). This project will use Xilinx ISE as a synthesis tool and ModelSim for the simulation tool. The result from this project will be compared with the result that had been obtained from the MATLAB.